PKPMPembinaan Kader Mubaligh/Mubalighat Muhammadiyah ‘Aisyiyah Dalam Kemajuan Dakwah Muhammadiyah Di Ranting Muhammadiyah Desa Sukasari Kec. Pegajahan - Mahmud Yunus Daulay; Nur Rahmah Amini (University of Muhammadiyah Sumatera Utara, 2019)
As a person who is in love with the Muhammadiyah organization, we must understand some of the Muhammadiyah movements that are the pioneers of the revival of the ummah. First, Muhammadiyah is the movement of Islam. Persyarikatan Muhammadiyah was built by KH Ahmad Dahlan as concrete results from the study and deepening (tadabbur) of the Alquranul Karim. This factor is actually the most important factor that drives the establishment of Muhammadiyah.From the founding background of Muhammadiyah as above, it is clear that the actual birth of Muhammadiyah was none other than inspired, motivated, and encouraged by the teachings of the Koran because it also had no other motives except solely to realize the principles of Islamic teachings. Everything that Muhammadiyah does, both in the fields of education and teaching, community, household, economy, and so on cannot be separated from efforts to realize and implement Islamic teachings. Strictly speaking, the Muhammadiyah movement wants to try to present the face of Islam in a real, concrete and tangible form, which can be experienced, felt, and enjoyed by the ummah as rahmatan lil’alamin.Thus, Muhammadiyah and Aisyiyah are movements of amar ma'ruf nahi munkar which are based on the Qur'an and the Sunnah.